A democratização da universidade pública: O impacto orçamentário na efetivação das políticas afirmativas no âmbito da UFT - Santos, Maurício Dias dos (Universidade Federal do Tocantins, 2020)
This work aims to understand the effectiveness of affirmative policies from restrictive measures in the budget forecast of the Federal University of Tocantins between 2016-2019, in the context of the democratization of public higher education. To this end, the critical-dialectical approach is adopted based on a qualitative and quantitative approach to microdata from official nationally consolidated research. The result of the investigation demonstrates that as the quota law tends to mirror the population composition, the University absorbs local sociodemographic factors, increasing its financial dependence on government transfers to maintain student assistance policies. This relationship reveals an acute symptom of the institutional crisis of the public university, since the gradual financial dependence coexists with the gradual process of budget restrictions, causing an emptying of affirmative policies as a whole.